2007
DOI: 10.1007/s11071-007-9228-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolutive and nonlinear vibrations of rotor on aerodynamic bearings

Abstract: The use of air as a lubricant in aerodynamic bearings is advantageous, particularly in the food industry. Aerodynamic bearings with tilting pads have complicated stiffness and damping properties and need a very detailed theoretical and experimental research. Response curves of rigid rotor supported on aerodynamic bearings are presented for a linear but evolutive mathematical model. Due to non-monotone properties of stiffness and damping matrices at variable revolutions, a new resonance appears. The mathematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Půst and Kozánek [13] have analyzed an aerodynamic tilting-pad bearing supporting a rigid rotor, and they have concluded that the inertia of pads has had a great influence on the bearing characteristics, and on the investigation of rotor vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Půst and Kozánek [13] have analyzed an aerodynamic tilting-pad bearing supporting a rigid rotor, and they have concluded that the inertia of pads has had a great influence on the bearing characteristics, and on the investigation of rotor vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently from the equations aerodynamic forces have three components: quasi-elastic, damping and non-conservative forces [2]. Differential equations of motion of system "rotor -ring" with account of aerodynamic forces can be written in the complex form (rotor displacement is 1 1…”
Section: Dynamics Of System "Rotor -Ring"mentioning
confidence: 99%
“…[4][5][6] Aerodynamic/hydrodynamic bearings present a relatively large wear rate during startup stage and have high requirements for design and processing. [7][8][9] Magnetic bearings can only act on magnetic materials and produce electromagnetic interference to precision instruments. 10,11 Therefore, starting from the new working principle, exploring new methods may be a way to expand the application field of non-contact bearings.…”
Section: Introductionmentioning
confidence: 99%